The Influence of Student Interest in Stock Investment in the Banking Sector: A Case Study at KSPMS Golden UIN Sumatera Utara - Hani, Hani Widari; Daulay, Aqwa Naser; Rahmani, Nur Ahmadi Bi (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2025)
This study aims to analyze the influence of financial literacy, risk perception, and minimum capital on students’ interest in investing in banking sector stocks. The research subjects are students and members of the Sharia Capital Market Study Group (KSPMS) Golden at the State Islamic University of North Sumatra. The research employed a quantitative associative approach with purposive sampling technique, involving 100 respondents. Data were analyzed using multiple linear regression with the assistance of SPSS version 30. The results show that financial literacy and minimum capital have a positive and significant effect on students' investment interest. In contrast, risk perception does not significantly affect investment interest. These findings indicate that increasing financial understanding and providing affordable capital can encourage more active student participation in stock investment, particularly in the banking sector. Therefore, the role of communities like KSPMS is crucial in educating and guiding students to become more knowledgeable and confident investors.